Use of veno-venous extracorporeal membrane oxygenation to treat severe combined calcium channel blocker and angiotensin converting enzyme inhibitor overdose. (March 2019) - Haughey, Ryan; Vernick, William; Gutsche, Jacob; Laudanski, Krzysztof
Introduction: Calcium channel blockers (CCBs) are a commonly prescribed medication that, at toxic levels, are capable of causing severe refractory hypotension, hypoxic respiratory failure and cardiotoxicity. There is little evidence currently guiding the approach to managing CCB overdose, particularly when combined with other antihypertensive agents. Case report: We describe the use of veno-venous extracorporeal membrane oxygenation (VV ECMO) in a previously healthy man following combined overdose with amlodipine and lisinopril in a suicide attempt. ECMO was used to provide oxygenation support, allowing for the amlodipine and lisinopril to be metabolized and cleared while also reducing ventilator-induced lung injury (VILI) and avoiding the complications associated with venous-arterial (VA) ECMO, such as differential hypoxemia. Conclusion: Limited case reports suggesting the use of ECMO in CCB overdose have employed VA ECMO due to CCB-induced cardiotoxicity. We believe that, if cardiac function has been preserved, VV ECMO should be considered a viable treatment strategy for CCB and ACE-I overdose resulting in refractory hypoxemic respiratory failure.